Association of cathepsin B and cystatin C with an age-related pulmonary subclinical state in a healthy Chinese population. (May 2020) - Wang, Nan; Yuan, Yajun; Bai, Xiaojuan; Han, Wen; Han, Lulu; Qing, Bijuan
Background: Cathepsin B (CTSB) and cystatin C (CYSC) are new biomarkers for several physiological and pathological processes as their activities increase with age. The aim of this study was to explore population-level associations between serum CTSB and CYSC with an age-related pulmonary subclinical state. Methods: We examined 401 healthy participants (aged 36–87 years, of which 44.3% were male) in northern Chinese cities. We used a standard spirometer to determine lung function. Serum CTSB and CYSC levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: For all participants, serum CTSB was related to maximum vital capacity (VC MAX), forced vital capacity (FVC), forced expiratory volume in 1 s, peak expiratory flow, forced expiratory flow at 25% of FVC, forced expiratory volume in 3 s (FEV3), and inspiratory vital capacity (VC IN). These associations were lost after full adjustment. CYSC remained significantly associated with inspiratory capacity (IC), breath frequency (BF; p  < 0.001), minute ventilation (MV), the ratio of FEV3 and FVC (FEV3%FVC), and expiratory reserve volume ( p  < 0.05) after adjusting for all other possible confounders. In males, serum CYSC levels exhibited significant and independent associations with FVC, FEV3 ( p  < 0.05), and IC ( p  < 0.001) and serum CTSB levels exhibited significant and independent associations with BF ( p  < 0.05). Conclusions: Our results confirmed serum CYSC concentration associations with an age-related lung function in healthy people. However, the association between serum CTSB and lung function was not well confirmed. Serum measurements of CYSC may provide valuable predictors of pulmonary function in healthy people, especially healthy elderly adults. The reviews of this paper are available via the supplemental material section .